Plant extract contact toxicities to various developmental stages of Colorado potato beetles (Coleoptera: Chrysomelidae) - Gokce, A.; Whalon, M. E.; Cam, H.; Yanar, Y.; Demirtas, I.; Goren, N. (WILEY, 2006)
The contact toxicities of methanol extracts from the nine plant species Hedera helix, Artemisia vulgaris, Xanthium strumarium, Humulus lupulus, Sambucus nigra, Chenopodium album, Salvia officinalis, Lolium temulentum and Verbascum songaricum were tested on the developmental stages of Colorado potato beetle (CPB) (Leptinotarsa decemlineata). About 2 mL of plant extract, 40% (w/w), was applied to the first instar to fourth instar larvae and adult beetles using a Potter spray tower. Most of the tested plant extracts caused relatively low mortality in all the beetle instars. Among the plant extracts, H. lupulus extract was the most toxic to all stages of the insect, except for the adult beetles. Larval mortality ranged from 40% in the fourth instars to 84% in the third instars. In a second series of experiments, dose-response bioassays using H. lupulus extract produced lethal concentration 50 (LC50) values ranging from 10%, 12%, 17% to 46% (w/w) active ingredient (plant material) for instars 1-4, respectively. This increasing mortality trend, however, did not extend to the adult stage where even the maximum dose of 40% plant material did not provide sufficient mortality to allow estimation of a LC50. These results demonstrated that the extract from H. lupulus has potential as an active ingredient in biological pesticides developed to manage larval instars of the CPB. The potential uses of this plant extract may be in conventional and organic pest management or as part of a mixture of plant extracts or conventional insecticides. Before extracts can be considered as biological control agents, their impact on natural enemies should be assessed.
Keywords: Artemisia; Chenopodium; Hedera; Humulus; Leptinotarsa decemlineata; Lolium; plant extract; potato crops; Salvia; Sambucus; Verbascum; Xanthium; DECEMLINEATA SAY COLEOPTERA; HOP BETA-ACIDS; INSECTICIDES; MANAGEMENT; RESISTANCE; SUSCEPTIBILITY; PESTS; Agriculture